Hyperostosis Frontalis Simulating Metastatic Deposits: Unmasked on SPECT-CT - Areeba Amin; Mairah Razi (Journal of the Pakistan Medical Association, 2024)
Skeletal scintigraphy has a pivotal role in detecting a number of bone pathologies, but it has its own limitations becauseof 2D image acquisition. Hybrid imaging acts as a savior in these cases where it is difficult to distinguish between benignand malignant lesions just on the basis of planar images. We present one such case of known breast carcinoma withabnormal increased radiotracer uptake in the skull which was difficult to characterize as benign lesion such as hyperostosisfrontalis or metastatic osseous lesion. The importance of describing this case is to have a thorough understanding ofhyperostosis patterns and to not confuse it with metastatic deposits in patients with known malignancies. Keywords: Hyperostosis Frontalis, SPECT-CT, bone scan